Implementation of Science Education for Junior High School Students in Lampung Province During the Covid-19 Pandemic - Tri Yuni Hendrowati; N Nurmitasari; Badrun Muhammad (Postgraduate, University of Mataram, 2023)
Science education is one of the important subjects in the scientific structure studied in our world of education. During the Covid-19 pandemic by considering the condition of the readiness of supporting infrastructure for online learning implementation, IT-based teacher skills, and online learning evaluation, this science subject was transformed to students. The purpose of this study is to describe the planning, organizing, implementing, and monitoring of Science Education, especially in public junior high schools in Lampung Province. This research is a qualitative research with an educational ethnography study design, and the research participants are principals of MKKS junior high schools in Lampung Province. This study used interviews, observations and documentation to collect data, which were then evaluated using the interactive model analysis. The findings of this study are as follows: (1) Natural Science lesson plans are prepared by taking into account student characteristics, materials, and the use of applications for learning implementation; (2) the organization of Natural Science learning begins with the formation of Whatsapp groups, the direction of learning meetings using Google Classroom and Google Meet by sharing links through Whatsapp groups; and (3) optimization of learning implementation in this science subject is still limited: 50% of public junior high schools in Lampung Province have limited internet bandwidth; (4) monitoring, science subject teachers have difficulty in conducting learning assessment because they cannot organize students in a perfect setting.